Continuous Electrochemical Synthesis of Iso‐Coumarin Derivatives from o‐(1‐Alkynyl) Benzoates under Metal‐ and Oxidant‐Free. Issue 60 (28th September 2020) - Lin, Xinxin; Fang, Zheng; Zeng, Cuilian; Zhu, Chenlong; Pang, Xinyan; Liu, Chengkou; He, Wei; Duan, Jindian; Qin, Ning; Guo, Kai
Abstract: A non‐oxidant and metal‐free strategy for synthesizing iso‐coumarin by using a continuous electrochemical microreactor to initiate an oxidative cyclization reaction of o ‐(1‐alkynyl) benzoate and radicals. This efficient and clean continuous electrosynthesis method not only avoids the complicated gas protection operation and production of by‐products in the batch processes, but also help to overcome the difficulty that batch metal catalysis and electrocatalysis are difficult to scale up, and has the potential for pilot‐scale experiment. Abstract : A novel method for the continuous synthesis of iso‐coumarin derivatives by selenization and self‐cyclization of alkynes through electrochemical oxidation under metal‐free and oxidant‐free conditions has been developed.